(untitled) (Research, Society and Development, 2023)
Dentistry students go through situations that demand a lot of their psychology and may be more susceptible to factors such as depression, anxiety, and stress. This study aimed to verify the therapeutic effects of rosemary essential oil (EO) on the mental health of a sample of students of the Dentistry course of a Federal University, in relation to clinical dental practice. A qualitative descriptive study was conducted. A structured questionnaire based on the Depression, Anxiety and Stress Scale (DASS-21) was used to evaluate the indices over time. The EO was applied topically twice a week for a period of 4 months with the help of a cotton pad. The sample consisted of 29 students, with a mean age of 24.5 years (±2.5) and most of them were women (65.5%). It was not possible to observe an association between age and scores, but the sample group is entirely composed of young adults of similar ages. Female participants had the highest scores of the factors analyzed. It was found that stress levels were more pronounced, followed by depression and finally anxiety. The results revealed that there were statistically significant effects on the reduction of scores. It was observed that the rosemary EO was effective in reducing the psychometric factors analyzed. Therefore, it is concluded that rosemary essential oil was able to promote improvements in the factors analyzed in the group of Dentistry students.